Identification of Genes Preferentially Expressed in Stomatal Guard Cells of Arabidopsis thaliana and Involvement of the Aluminum-Activated Malate Transporter 6 Vacuolar Malate Channel in Stomatal Opening - Ye, Wenxiu; Koya, Shota; Hayashi, Yuki; Jiang, Huimin; Oishi, Takaya; Kato, Kyohei; Fukatsu, Kohei; Kinoshita, Toshinori (Frontiers in Plant Science, 2021)
Stomatal guard cells (GCs) are highly specialized cells that respond to various stimuli, such as blue light (BL) and abscisic acid, for the regulation of stomatal aperture. Many signaling components that are involved in the stomatal movement are preferentially expressed in GCs. In this study, we identified four new such genes in addition to an aluminum-activated malate transporter, ALMT6, and GDSL lipase, Occlusion of Stomatal Pore 1 (OSP1), based on the expression analysis using public resources, reverse transcription PCR, and promoter-driven β-glucuronidase assays. Some null mutants of GC-specific genes evidenced altered stomatal movement. We further investigated the role played by ALMT6, a vacuolar malate channel, in stomatal opening. Epidermal strips from an ALMT6-null mutant exhibited defective stomatal opening induced by BL and fusicoccin, a strong plasma membrane H+-ATPase activator. The deficiency was enhanced when the assay buffer [Cl–] was low, suggesting that malate and/or Cl– facilitate efficient opening. The results indicate that the GC-specific genes are frequently involved in stomatal movement. Further detailed analyses of the hitherto uncharacterized GC-specific genes will provide new insights into stomatal regulation.